2020
DOI: 10.1101/2020.10.09.20209775
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with progression to critical illness in 28 days among COVID-19 patients: results from a tertiary care hospital in Istanbul, Turkey

Abstract: Background Coronavirus disease 2019 (COVID-19) quickly spread worldwide to become a pandemic. This study aimed to define the predictors of critical illness development within 28 days postadmission. Methods We conducted a prospective cohort study including 477 PCR-positive COVID-19 patients admitted to a tertiary care hospital in Istanbul from March 12 to May 12, 2020. The development of critical illness, e.g., invasive mechanical ventilation and/or death, was followed for a period of 28 days postadmission. De… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Although the primary target of our study was to describe the serum concentration–time profile and pharmacokinetic features of favipiravir, follow‐up of the laboratory parameters of the COVID‐19 patients indicated a significant increase in ferritin levels in the deceased patients, whereas there was a significant decrease in D‐dimer and C‐reactive protein levels in the surviving patients at Day 0 compared to Day 5. In previous studies, COVID‐19 patients with elevated inflammatory markers have been reported to have worse prognosis of disease and our results are compatible with such findings in the literature 10,18,23,25,26 . A recent observation indicated a hyper‐inflammatory state in COVID‐19, which is related to hyperdynamic state with high cardiac output and increased renal perfusion due to vasodilatation, which results in augmented renal clearance and speeds the elimination of renally cleared drugs 19,27 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the primary target of our study was to describe the serum concentration–time profile and pharmacokinetic features of favipiravir, follow‐up of the laboratory parameters of the COVID‐19 patients indicated a significant increase in ferritin levels in the deceased patients, whereas there was a significant decrease in D‐dimer and C‐reactive protein levels in the surviving patients at Day 0 compared to Day 5. In previous studies, COVID‐19 patients with elevated inflammatory markers have been reported to have worse prognosis of disease and our results are compatible with such findings in the literature 10,18,23,25,26 . A recent observation indicated a hyper‐inflammatory state in COVID‐19, which is related to hyperdynamic state with high cardiac output and increased renal perfusion due to vasodilatation, which results in augmented renal clearance and speeds the elimination of renally cleared drugs 19,27 .…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, COVID-19 patients with elevated inflammatory markers have been reported to have worse prognosis of disease and our results are compatible with such findings in the literature. 10,18,23,25,26 A recent observation indicated a hyperinflammatory state in COVID-19, which is related to hyperdynamic state with high cardiac output and increased renal perfusion due to vasodilatation, which results in augmented renal clearance and speeds the elimination of renally cleared drugs. 19,27 Therefore, monitoring drug concentration of renally eliminated drugs can be advised in critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with survivors, non-survivors had lower DBP (78.0 vs. 70.0; p=0.0039), lower sO2 (93.0 vs. 87.5; p<0.0001), and higher RR (28.0 vs. 36.0; p=0.0002). In another study conducted in our instutituon, body temperature ≥38°C, RR ≥22/min, and sO2 ≤93% were revealed to be related with progression to critical illness among COVID-19 patients [ 16 ]. In our study, we recorded the variables as continuous variables instead of categoric, contrary to the study mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Döngü eşik değeri; yüksek (<20), orta (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) ve düşük (>30) olarak kategorize edildi. Yatan hasta kohortuna ait veriler ayrı bir çalışma yapılarak yayımlandı (17). Çalışmadaki bağımsız değişkenler, yukarıda sözü edilen standart formdaki kayıtlı verilerden elde edildi.…”
Section: Yöntemlerunclassified